5PSQ-010 Identification of incorrect dosing of direct oral anticoagulants: an important intervention to improve patient safety. (23rd March 2022) - Nagele, F; Tudela-Lopez, E; Hana, M; Holbik, M; Zotter, S; Amtmann, M; Datterl, B; Pölzleitner, P; Jadrna, K; Stemer, G; Anditsch, M
Abstract : Background and importance: Incorrect dosing of direct oral anticoagulants (DOACs) potentially increases the risk of bleeding or thromboembolic events. For guideline-conforming dosing [1] multiple factors such as indication, age, body weight, renal function, drug interactions and risk of bleeding have to be considered. Therefore, correct dosing of DOACs represents a challenge in clinical practice. Aim and objectives: This study aimed to quantify DOAC dosing errors, identify barriers of correct dosing, assess potential reasons for errors and to investigate the acceptance rate of pharmaceutical interventions addressing dosing errors. Material and methods: During a 6-month study period (April–September 2021) all DOAC prescriptions of clinical pharmacist (CP)-reviewed patients in a 1740 bed tertiary care hospital were prospectively collected. Prescriptions were assessed for dosing errors and, if necessary, corrections were recommended to prescribers. Doses according to Summary of Product Characteristics (SPC) criteria were considered correct. A total of 813 beds on 44 different wards (including surgical and internal medicine patients) were covered by 17 CPs. Results: Dosing checks were performed in 811 patients (44.5% women, median age 78 years, median estimated glomerular filtration rate (eGFR) Modificaiton of Diet in Renal Disease (MDRD) 60 mL/min/1.73 m 2 ). A total of 194 incorrect doses (23.9%) were identified. The most common DOAC indication was atrial fibrillation (76.2%). The most frequently evaluated DOAC was edoxaban (31.1%). A significant relation was found between apixaban 2×2.5 mg (X 2 (1, N = 123) = 18.1, p<0.001) as well as dabigatran 2×150 mg (X 2 (1, N = 40) = 5.95, p = 0.015) and incorrect dosing. A risk factor significantly related with incorrect dosing was age above 80 years (X 2 (1, N = 351) = 7.0, p = 0.008). 45.9% of dosing errors were corrected following a pharmaceutical intervention. A common reason given for incorrect dosing was 'unstable renal function'. Conclusion and relevance: This study showed that DOAC dosing errors are frequent and pharmaceutical interventions can contribute to a reduction of these errors. Special caution is needed in elderly patients. Measures to increase acceptance rate need to be further investigated. References and/or acknowledgements: 1. Steffel, J, Collins, R, Antz, M, et al. European Heart Rhythm Association practical guide on the use of non-vitamin k antagonist oral anticoagulants in patients with atrial fibrillation. EP Europace 2021;23 (10):1612–1676. Conflict of interest: No conflict of interest